2005
DOI: 10.1103/physrevb.71.041405
|View full text |Cite
|
Sign up to set email alerts
|

Physical origin of directional beaming emitted from a subwavelength slit

Abstract: We propose the physical origin for a directional beam of light emitting from a single subwavelength slit in metallic film that is characterized by a corrugation feature at the exiting side of the film. We theorize that the beaming phenomenon can be explained simply as surface plasmon diffraction along the corrugation as long as the multiple scattering effects are taken into account to restate the dispersion relationship of the surface plasmon. In order to prove our theory, both an experimental setup and numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(57 citation statements)
references
References 34 publications
(18 reference statements)
3
54
0
Order By: Relevance
“…One period of this oscillation is comparable to the SPP wavelength (~380 nm) on the metal surface, which again confirms that the SPP propagation on the top metal surface has a key role in the beam formation 26 . The magnitude of g determines the phase that SPPs pick up in travelling from the central slit to the first groove.…”
Section: Confocal Scanning Images Of the Collimated Fluorescent Emisssupporting
confidence: 64%
“…One period of this oscillation is comparable to the SPP wavelength (~380 nm) on the metal surface, which again confirms that the SPP propagation on the top metal surface has a key role in the beam formation 26 . The magnitude of g determines the phase that SPPs pick up in travelling from the central slit to the first groove.…”
Section: Confocal Scanning Images Of the Collimated Fluorescent Emisssupporting
confidence: 64%
“…One of the typical works is the presentation regard ing the control of beaming through the subwavelength metallic slits reported by Yu et al in Ref. [16][17][18]. In their discussion, they confirmed that convergence and diver gence of the beaming after the slits are determined by the relationship between the wave vector k SP and item of 2π/Λ, where Λ is the period of the corrugated structure on metal film, as shown in Figure 1A-C.…”
Section: Introductionsupporting
confidence: 61%
“…Thus the re-emitted light has a wavevector normal to the laser facet (u ¼ 0). At the same frequency, the wavevector of the SPs on a metal surface patterned with a grating (k sp -grating ) is larger than the wavevector of the SPs on a planar metal surface (k sp -planar ) 13 , which is almost equal to the free-space wavevector k o in the mid-infrared region of the spectrum. As a result, the grating period L (¼8.9 mm) should be smaller than the free-space wavelength (L ¼ 2p/k sp -grating , 2p/k sp -planar % 2p/k o ¼ l o ¼ 9.9 mm) in order to generate a collimated beam normal to the laser facet.…”
Section: Methods Design Considerations For the Slit-grating Plasmonicmentioning
confidence: 98%
“…There have been subsequent theoretical and experimental studies of this aperture -groove structure [10][11][12][13][14] , but there have been very few attempts to integrate this structure into an active device [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%